Implementasi Pemikiran Imam Al-Ghazali tentang Pendidikan Karakter - Andika Dirsa; Intan Kusumawati (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The purpose of this study was to determine the implementation of character education in early childhood. Character education is an ongoing process, the goal to be achieved by character education is the implementation of the exemplary values formed in each human person as a social being. The purpose of character education desired by Imam Al-Ghazali is taqarrub ilallah and perfection to achieve happiness in the life of the world and the hereafter. Imam Al-Ghazali's thoughts on character education always show the morality and spirituality side. The results achieved in this study that the implementation of character education in early childhood which according to Imam Al-Ghazali is a thought that is based on habituation that starts from giving examples and exercises, in order to form good morals as a basis for the formation of dignified human character.